Pengelompokan wilayah produksi tuna, cakalang, tongkol dan udang di Indonesia menggunakan algoritma K-Means - Dwiasnati, Saruni; eliyani, Eliyani; Arif, Sutan Mohammad; Avrizal, Reza (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
The research was intended to cluster the production areas of Indonesia's fishery products especially Skipjack Tuna, Tuna, Mackarel Tuna, and shrimp using data science techniques. The algorithm used was K-means Clustering. The data used was annual production data for each province for the last 3 years (2019 – 2021). Determination of the number of clusters using the Elbow Method. For each commodity, three clusters were obtained, namely clusters with low production, medium production, and high production. For Skipjack Tuna, there were 19 provinces belonging to the low cluster, 13 provinces being medium, and 2 provinces being high. For Tuna, there were 22 provinces in the low cluster, 9 provinces in the middle, and 3 provinces in the high cluster. For Mackarel Tuna, low was 19 provinces, medium was 12 provinces, and high was 3 provinces. For shrimp, 23 provinces were low, 7 provinces were medium, and 4 provinces were high. High production clusters for Skipjack Tuna were North Sulawesi and North Maluku Provinces, Tuna were North Sulawesi, North Maluku and Maluku Provinces, for Mackarel Tuna were Aceh, East Java and Maluku Provinces, and for shrimp were North Sumatra, West Kalimantan, South Kalimantan and East Kalimantan Provinces.